ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' LEARNING ACTIVITY IN DIFFERENTIATED MATHEMATICS LEARNING - Trisnani, Novy (Elementary School Teacher, 2025)
Learning activity enhances learning effectiveness, including in differentiated instruction. This study analyzes student learning activity in mathematics using a differentiated approach in elementary schools. The research employs a qualitative descriptive method with one mathematics teacher and 25 fifth-grade students at SD Negeri Tanjungharjo. Data were collected through observation, interviews, and document analysis, then analyzed through data collection, reduction, presentation, and conclusion drawing. Observations show that differentiated mathematics learning has been well implemented. Key strengths include the availability of diverse learning resources, which are widely accessible and effectively utilized, and the provision of personalized and constructive feedback that supports student learning. However, challenges remain in defining clear and adaptable differentiated learning objectives and managing time effectively during lessons. Student activity is most evident in listening, where students show full engagement, while writing activities are less prominent, and oral participation remains moderate. Interviews indicate benefits such as increased engagement and better concept comprehension. Challenges include limited teacher training, varying student abilities, and restricted time for personalized instruction. Documentation analysis confirms alignment with differentiated learning principles, though inconsistencies exist. Challenges include time constraints, student ability differences, and resource needs. Teachers should undergo further training and refine time management strategies to enhance student engagement effectively.